1986
DOI: 10.3109/00016488609132835
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal Thiol Proteases (Cathepsin B-like Proteases) in Serous Middle Ear Effusions from Adult Patients

Abstract: Hydrolytic activity of cathepsins B, H and trypsin-like proteases was measured in 38 serous middle ear effusion (MEE) samples. The concentrations of (alpha 1-AT) and alpha 2-macroglobulin (alpha 2-M) were also quantitated. The mean value of cathepsin B activity was 25.0 +/- 20.7 RFU and that of cathepsin H was 14.3 +/- 3.0--both significantly higher than those in plasma (1.8 +/- 0.4 RFU, 1.2 +/- 0.3 RFU, p less than 0.005). Very low trypsin-like protease activity could be observed. The mean concentrations of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The potential endogenous production of pepsinogen in the middle ear mucosa also needs to be ruled out in order to establish reflux as the mechanism for finding pepsin or pepsinogen in middle ear fluid. Several groups of investigators have established that the production of enzymes may be induced in the middle ear during acute infections and with chronic effusions, 18–20 so that it is possible that the production of pepsinogen may also be inducible in the middle ear. Isozymogens of pepsinogen have been identified in other tissues in the body other than the stomach, including intestine, lung, pancreas, prostate, and some malignancies 21 .…”
Section: Discussionmentioning
confidence: 99%
“…The potential endogenous production of pepsinogen in the middle ear mucosa also needs to be ruled out in order to establish reflux as the mechanism for finding pepsin or pepsinogen in middle ear fluid. Several groups of investigators have established that the production of enzymes may be induced in the middle ear during acute infections and with chronic effusions, 18–20 so that it is possible that the production of pepsinogen may also be inducible in the middle ear. Isozymogens of pepsinogen have been identified in other tissues in the body other than the stomach, including intestine, lung, pancreas, prostate, and some malignancies 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have reported that the endotoxin level in MEE is one of the parameters reflecting the chronicity of OME in children.>:" Lysosomal proteases in the middle ear mucosa and MEE have been shown to play significant roles during the disease processes of OME, because their proteolytic activity causes tissue damage and prolongs middle ear inflammation by activating proenzymes (kininogen and plasminogen) and the complement system. [9][10][11] Lysosomal proteases seem to suppress the recovery from acute OME unless they are inactivated by protease inhibitors. 12 .…”
Section: Introductionmentioning
confidence: 99%